Vibrational biospectroscopy characterizes biochemical differences between cell types used for toxicological investigations and identifies alterations induced by environmental contaminants - Heys, Kelly A.; Shore, Richard F.; Pereira, M. Glória; Martin, Francis L. (Environmental toxicology and chemistry, 2017)
The use of cell‐based assays is essential in reducing the number of vertebrates used in the investigation of chemical toxicities and in regulatory toxicology assessment. An important factor in obtaining meaningful results that can be accurately extrapolated is the use of biologically appropriate cell lines. In the present preliminary study, attenuated total reflection–Fourier transform infrared (ATR–FTIR) spectroscopy with multivariate analysis was used to assess the fundamental biomolecular differences between a commonly used cell line, MCF‐7 cells, and an environmentally relevant cell line derived from mallard (Anas platyrhynchos) dermal fibroblasts. To better understand differences in basic cell biochemistry, the cells were analyzed in the untreated state or post exposure to polychlorinated biphenyl (PCB) and polybrominated diphenyl ester (PBDE) congeners. The main spectral peaks in spectra from both cell types were associated with cellular macromolecules, particularly proteins and lipids, but the spectra also revealed some cell‐specific differences. Spectra from untreated mallard fibroblasts spectra contained a large peak associated with lipids. The cell‐related differences in lipids and deoxyribonucleic acid (DNA) were also identified as regions of spectral alteration induced by PBDE and PCB exposure. Although lipid alterations were observed in post treatment spectra from both cell types, these may be of more significance to mallard fibroblasts, which may be the result of increased intracellular lipid as determined by Nile red staining. Untreated MCF‐7 cell spectra contained unique peaks related to DNA and nucleic acids. The DNA‐associated spectral regions were also identified as areas of considerable alteration in MCF‐7 cells exposed to some congeners including PBDE 47 and PCB 153. The findings indicate that in their native state, MCF‐7 and mallard cells have unique biochemical differences, which can be identified using ATR–FTIR spectroscopy. Such differences in biochemical composition may influence cell susceptibility to environmental contaminants and therefore influence the choice of cell type used in toxicology experiments. To our knowledge, the present study is the first study to analyze the biochemistry of a mallard dermal fibroblast cell line and to use ATR–FTIR spectroscopy for this purpose. Thus ATR–FTIR spectroscopy is demonstrated to be a useful tool for exploration of biomolecular variation at the cellular level and with further development, it could be used as part of a panel of cell‐based assays to indicate when different results might be seen in environmental species compared with currently used cell lines. Environ Toxicol Chem 2017;36:3127–3137. © 2017 SETAC